1985
DOI: 10.1038/bjc.1985.6
|View full text |Cite
|
Sign up to set email alerts
|

“Concomitant immunity” in murine tumours of non-detectable immunogenicity

Abstract: Summary Various immunization assays were used to demonstrate the lack of immunogenicity of three BALB/c tumours of spontaneous origin and of a fourth one resulting from foreign body tumorigenesis. All four tumours inhibited the growth of a second implant of the same tumour into the contralateral flank. In our tumour models "concomitant immunity" (1) was not mediated by macrophage or T-cell dependent immune reactions: both thymectomized BALB/c and nude mice (treated or untreated with silica) gave the same resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 14 publications
(4 reference statements)
3
68
0
1
Order By: Relevance
“…In effect, concomitant resistance induced by strongly immunogenic tumours has been described as tumour specific and mainly mediated by T-cell-dependent cytotoxic mechanisms, not different from a classical immunological rejection (Belehradek et al, 1972;Chandradasa, 1973;Tuttle et al, 1983;North, 1984;Akporiaye et al, 1988). On the other hand, concomitant resistance induced by weakly or non-immunogenic tumours has been described as non-specific and mediated by a cytostatic mechanism presumably unrelated to any known conventional immunological mechanism (Gorelik et al, 1981;Gorelik, 1983;Ruggiero et al, 1985;Meiss et al, 1986;Bonfil et al, 1988). In a former paper (Ruggiero et al, 1990) we demonstrated that the serum from mice bearing non-immunogenic tumours exhibited a growth-inhibitory activity (not attributable to cytotoxic antibodies) on in vitro proliferation of tumour cells that was proportional to the intensity of concomitant resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In effect, concomitant resistance induced by strongly immunogenic tumours has been described as tumour specific and mainly mediated by T-cell-dependent cytotoxic mechanisms, not different from a classical immunological rejection (Belehradek et al, 1972;Chandradasa, 1973;Tuttle et al, 1983;North, 1984;Akporiaye et al, 1988). On the other hand, concomitant resistance induced by weakly or non-immunogenic tumours has been described as non-specific and mediated by a cytostatic mechanism presumably unrelated to any known conventional immunological mechanism (Gorelik et al, 1981;Gorelik, 1983;Ruggiero et al, 1985;Meiss et al, 1986;Bonfil et al, 1988). In a former paper (Ruggiero et al, 1990) we demonstrated that the serum from mice bearing non-immunogenic tumours exhibited a growth-inhibitory activity (not attributable to cytotoxic antibodies) on in vitro proliferation of tumour cells that was proportional to the intensity of concomitant resistance.…”
mentioning
confidence: 99%
“…It was maintained by s.c. serial passages in syngeneic mice and was used between passages 69 and 170. More detailed description of this tumour is given elsewhere (Ruggiero et al, 1985;Zahalka et al, 1993).…”
mentioning
confidence: 99%
“…Tumour LB is a T-cell leukaemia, which spontaneously arose in a BALB/c mouse and has been maintained by serial passages in the peritoneal cavity of syngeneic hosts (Ruggiero et al, 1984;Alvarez et al, 1989;Lugasi et al, 1990). LBC is an established cell line derived from LB leukaemia (Mongini et al, 1991).…”
Section: Micementioning
confidence: 99%
“…In previous work we have reported the establishment and characterisation of the LBC cell line (Mongini et al, 1991) derived from the original T-cell leukaemia LB (Ruggiero et al, 1984). LBC cells express the following surface markers: Thy-1, Lyt-2 (CD 8), CD 41ow+ CD 25 (IL-2 receptor, a chain), class I (Kd and Dd), but not class II (I-Ad, I-Ed) gene products.…”
mentioning
confidence: 99%
“…The T-helper cell leukaemia (LB), which arose spontaneously in a 6-month-old Balb/c male mouse (Ruggiero et al, 1985) was, at the beginning of this study, in its 58th s. …”
Section: Tumourmentioning
confidence: 99%